Co-Designing a Mobile App to Improve Mental Health and Well-Being: Focus Group Study - Alqahtani, Felwah (JMIR Form Res, 2021)
BACKGROUND: Recent advances in mobile technology have created opportunities to develop mobile apps to aid and assist people in achieving various health and wellness goals. Mental health apps hold significant potential to assist people affected by various mental health issues at any time they may need it, considering the ubiquitous nature of mobile phones. However, there is a need for research to explore and understand end users’ perceptions, needs, and concerns with respect to such technologies. OBJECTIVE: The aim of this paper is to explore the opinions, perceptions, preferences, and experiences of people who have experienced some form of mental health issues based on self-diagnosis to inform the design of a next-generation mental health app that would be substantially more engaging and effective than the currently available apps to improve mental health and well-being. METHODS: We conducted six focus group sessions with people who had experienced mental health issues based on self-diagnosis (average age 26.7 years, SD 23.63; 16/32, 50% male; 16/32, 50% female). We asked participants about their experiences with mental health issues and their viewpoints regarding two existing mental health apps (the Happify app and the Self-Help Anxiety Management app). Finally, participants were engaged in a design session where they each sketched a design for their ideal mental health and well-being mobile app. RESULTS: Our findings revealed that participants used strategies to deal with their mental health issues: doing something to distract themselves from their current negative mood, using relaxation exercises and methods to relieve symptoms, interacting with others to share their issues, looking for an external source to solve their problems, and motivating themselves by repeating motivational sentences to support themselves or by following inspirational people. Moreover, regarding the design of mental health apps, participants identified that general design characteristics; personalization of the app, including tracking and feedback, live support, and social community; and providing motivational content and relaxation exercises are the most important features that users want in a mental health app. In contrast, games, relaxation audio, the Google map function, personal assistance to provide suggestions, goal setting, and privacy preservation were surprisingly the least requested features. CONCLUSIONS: Understanding end users’ needs and concerns about mental health apps will inform the future design of mental health apps that are useful to and used by many people.